Mechanism for Issuing a Doctor's Practice License in Health Law No. 17 of 2023 - Wulandari, Eka; Budhiartie, Arrie (Veteran Law Review, 2025)
Doctors are a profession with a crucial role in providing healthcare services and efforts for the community in Indonesia. To practice, a doctor must first obtain a Practice License, referred to as SIP, as proof of professionalism. To acquire an SIP, a doctor must go through several procedures, including educational registration, qualification verification, administrative review, and professional competency assessment. Following the enactment of Law No. 17 of 2023 concerning Health, there are notable changes, one of which pertains to the SIP issuance procedure, which differs from the previous law. This normative study examines the changes using a legislative approach, comparing the provisions in the new Health Law with the old one. The aim of this research is to understand the mechanism for issuing a doctor’s SIP after the implementation of Law No. 17 of 2023. After reviewing several normative research sources, the author found that there are changes in the SIP issuance mechanism under the new Health Law. These differences include the requirements doctors must fulfill to obtain an SIP, where the new Health Law no longer requires a recommendation letter from a professional organization as a prerequisite for obtaining an SIP.